State Governance and the Crisis of National Development in Nigeria - AFONUGHE, Irikefe Omamuyovwi (Management Research and Behavior Journal, 2024)
Nigerian governments have undertaken a number of risky projects over the years to address the populace's strong desire for improved living standards and national growth. This ongoing ambition also made it necessary for the various administrations to come up with a number of development plans that were targeted at the solution. Because of this, this study specifically looked at how national development and governance fit into the picture as the only factors that affect the pipe's tone. However, it is important to stress that when a problem and its origin are well understood, a solution is almost always close at hand. For this reason, the study is heavily focused on concerns pertaining to Nigeria's lack of progress. The study, which mainly relied on the qualitative method of data collection, selected the social development theory as the focal compass to explore the challenges of governance and the national development crises in Nigeria. The study's conclusions show several developmental plans with their own unique conception, goal, perspective, and engineering apparatus. However, a number of these schemes shared a history of inefficiency and structural shortcomings, which made it more difficult for Nigeria to achieve development. The government's inability to implement successful development is due to a number of factors, including poor state institutions, a lack of political will, and various obsolete developmental strategies. The report also suggested that the only things that may truly advance a country's growth are political will, the merit system, stability and continuity of policy programs, and the adoption of the philosophies of the Japanese and Chinese.